A Comparative Evaluation of Different Irrigation Activation Techniques on Root Canal Cleanliness: A Scanning Electron Microscope Study - Ahmad, Lubna; Bhasin, Prashant; Kumar, Hemanshi; Vats, Vrinda; Madan, Prateek; Tandan, Monika (European Journal of Dentistry, 2025)
This article compares the effect of ultrasonic, sonic activation of intracanal heated 3% sodium hypochlorite and laser-activated 3% sodium hypochlorite (NaOCl) on root canal cleanliness using scanning electron microscope.Eighty-eight permanent mandibular premolars were extracted and decoronated to obtain 14 mm of standardized root length. Working length was calculated and canals were prepared till size 25/0.04. Samples were randomly divided into four groups according to the method of irrigation employed (n = 22)—group A: passive ultrasonic irrigation (PUI) of 3% intracanal heated NaOCl, group B: sonic activation of 3% intracanal heated NaOCl, group C: activation of 3% NaOCl by diode laser, and group D: conventional needle irrigation (CNI). Samples were split into two halves and the presence of debris at these regions was graded under scanning electron microscope. The chi-square test was employed to assess significant differences in cleanliness scores and pairwise comparisons using the Dunn test were performed to identify specific group difference. A p-value of < 0.05 was kept as level of significance for all analysis.Group A and group B showed maximum cleanliness in middle third as compared with apical third. Group C (laser) showed better cleanliness in apical third as compared with middle third. While group D (CNI) irrigation showed the lowest cleaning efficiency both in the middle third and apical third.It was concluded that PUI with intracanal heating of 3% NaOCl and diode laser activation of 3% NaOCl can be recommended as a potential irrigant activation strategy to effectively clean inaccessible areas of the root canal system.
Keywords: diode laser; root canal cleanliness; scanning electron microscope; sonic; ultrasonic activation